Réponses

2014-02-17T03:59:26+01:00


13x + 2 - ( x - 3 ) = x  - 5 - 3 ( x + 12 ) + 4x

13x + 2 - x + 3 = x - 5 - 3x -36 + 4x

12x + 5 = 2x - 41

12x - 2x = -41 - 5

10x = -46

x = -46/10

x = - 23/5

2014-02-17T05:02:03+01:00
     13x + 2 - x -3 = -5 -3x - 36 + 4 x                                                                                             12x -1 = -41 - 1x                                                                                                                12x -1 + 1x = -41 -1x + 1x                                                                                                       13x -1= -41                                                                                                                      13x -1 + 1 = -41 + 1                                                                                                               13x = -40                                                                                                                         13x / 13 = -40/ 13                                                                                                               x= -40 / 13 
j'ai utilisé la méthode de la balance avec deux variables ! j'espère que je t'ai aider :)